The effect of yoga on insomnia and quality of life among nursing professionals during COVID-19: A pre–post-test interventional study - Madhu Basavegowda; Sujan M. Umeshchandra; Patteswari Duraisamy; Rajesh K. Thimmulappa; Mounika S. Manivasagan; Chaithra Mallaiah; Jahnavi V. Madhu; Vijaya V. Yogeeshwaran; Nagashree Vishwanath; Vinitha K. Rudramuniyappa; Srinath C. Galag; VSK Manasa Priya Dwadasi (Indian Journal of Psychiatry)
Background: The coronavirus disease 2019 (COVID-19) pandemic has taken a toll on the well-being and quality of life (QoL) of healthcare professionals, especially nurses. Insomnia, a common consequence of the pandemic, adds to the physical and mental strain on healthcare workers. Aim: This study aimed to assess the impact of workplace yoga intervention on insomnia severity and QoL among female nursing and healthcare professionals during the pandemic. Methods: A pre–post-interventional study was conducted among 173 nursing professionals working in a hospital setting. Baseline assessments collected age, body mass index (BMI), insomnia severity using the Insomnia Severity Index (ISI), and QoL using the World Health Organization Quality-of-Life Brief Version (WHOQOL-BREF). A 6-week workplace yoga intervention was conducted by trained professionals, followed by posttest assessments. Results: Among 173 participants, 57 had insomnia. Participants without significant insomnia had higher QoL scores (P < 0.001). Following the yoga intervention, both subthreshold and moderate clinical insomnia groups experienced reduced insomnia severity (P < 0.001). Quality-of-life scores in the physical, psychological, and environmental domains improved significantly (P < 0.05). Conclusion: Workplace yoga intervention appears to be a promising approach to alleviate insomnia and enhance QoL among female nursing and healthcare professionals during the COVID-19 pandemic. Implementing tailored workplace yoga programs can play a crucial role in promoting the well-being and resilience of healthcare workers, contributing to a positive work environment and improved patient care outcomes.